2018
DOI: 10.1177/1940082918818401
|View full text |Cite
|
Sign up to set email alerts
|

Hits Close to Home: Repeated Persecution of King Cobras (Ophiophagus hannah) in Northeastern Thailand

Abstract: Protected areas are often promoted as an important solution to preserving biodiversity. However, permeable edges can undermine the effectiveness of preserves because animals may move into adjacent human-dominated unprotected areas. We investigated attitudes toward, and sources of mortality of, a far-ranging apex predator, the king cobra (Ophiophagus hannah; Cantor 1836), in a biosphere reserve in northeastern Thailand. Our questionnaire revealed marked fear of snakes and hostility toward king cobras. Using rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 85 publications
1
46
0
Order By: Relevance
“…Vulnerability in anthropogenic landscapes can be augmented by species traits such as large body size, 55 parental investment in offspring, habitat specialisation, and low population densities, which have been 56 connected to increased extinction risk ( Todd et al 2017). Species frequently involved in human-wildlife conflict are also more 58 vulnerable to direct mortality in anthropogenic landscapes (Shankar et al 2013, Marshall et al 2018. 59…”
Section: Introduction 35mentioning
confidence: 99%
See 3 more Smart Citations
“…Vulnerability in anthropogenic landscapes can be augmented by species traits such as large body size, 55 parental investment in offspring, habitat specialisation, and low population densities, which have been 56 connected to increased extinction risk ( Todd et al 2017). Species frequently involved in human-wildlife conflict are also more 58 vulnerable to direct mortality in anthropogenic landscapes (Shankar et al 2013, Marshall et al 2018. 59…”
Section: Introduction 35mentioning
confidence: 99%
“…The transitional zone also contains 159 villages and a four-lane highway that 74 connects Nakhon Ratchasima to Bangkok. Further descriptions of the study site can be found in Silva 75 et al (2018) and Marshall et al (2018Marshall et al ( , 2019. 76…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The nature of these captures serves as evidence that Burmese pythons do initiate humanwildlife conflict via consumption of livestock in our study site. We were fortunate that none of these instances led to the persecution of Burmese pythons, as direct human-snake conflict results in snake mortality for other species in our study site (Crane et al, 2016;Marshall et al, 2018). It is difficult to determine whether Burmese pythons fall victim to persecution in our study site as we suspect that people would hesitate to notify us about killing or harming a protected species.…”
Section: Discussionmentioning
confidence: 92%